2018
DOI: 10.2147/tcrm.s162690
|View full text |Cite
|
Sign up to set email alerts
|

Is ischemia-modified albumin a reliable tool for the assessment of acute pancreatitis?

Abstract: PurposeOxidative stress has been implicated in several disorders, including acute pancreatitis (AP). Ischemia-modified albumin (IMA), which reflects the ability to bind cobalt, has been found to be elevated in conditions of oxidative stress and tissue hypoxia. This study examined IMA and adjusted IMA levels in patients with AP, and examined the associations of IMA and adjusted IMA levels to the severity of AP.Patients and methodsA total of 42 consecutive patients with AP and 43 age- and sex-matched control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Hypoalbuminemia has been described as a negative prognostic factor in several diseases, [ 89 92 ]. Furthermore, low serum albumin concentrations have been shown to be associated with the severity of chronic inflammatory diseases, inflammatory bowel disease and diabetes mellitus [ 93 ], cirrhosis [ 94 ], as well as with the severity of surgical trauma [ 95 ], acute diseases [ 96 ] and sepsis [ 97 ]. In addition, in past SARS epidemics, hypoalbuminemia has been shown to be related with disease severity and increased hospital mortality [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia has been described as a negative prognostic factor in several diseases, [ 89 92 ]. Furthermore, low serum albumin concentrations have been shown to be associated with the severity of chronic inflammatory diseases, inflammatory bowel disease and diabetes mellitus [ 93 ], cirrhosis [ 94 ], as well as with the severity of surgical trauma [ 95 ], acute diseases [ 96 ] and sepsis [ 97 ]. In addition, in past SARS epidemics, hypoalbuminemia has been shown to be related with disease severity and increased hospital mortality [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and the production of free radicals are responsible for the progression of pancreatic inflammation, and triggering the generation of inflammatory cytokines is the key event in the pathogenesis of acute pancreatitis. [18] We concluded that thiol-disulphide levels decreased as oxidative stress increased in acute pancreatitis. This study aims to compare the thiol-disulphide homeostasis and other blood parameters levels of patients with AP and healthy controls, and to investigate thiol-disulphide homeostasis as a marker of disease severity.…”
Section: Discussionmentioning
confidence: 83%
“…The results of this study showed that ISO had neurotoxicity and could induce HT22 hippocampal neuronal cell death and inhibit cell survival in a dose-dependent man- ner. ROS is a by-product produced in the process of normal cell metabolism [30]. Under physiological station, there is a dynamic balance between the ROS accumulation system and antioxidant scavenging system [31].…”
Section: Discussionmentioning
confidence: 99%